Combined Therapy of Patients with Recurring Anogenital Herpes Infection - M. R. Rakhmatulina (Антибиотики и Химиотерапия, 2020)
Up-to-date conceptions of etiology and epidemiology of anogenital herpetic infection are described. The main mechanisms of immunological shifts in subjects with anogenital Herpes infection are discussed. The efficacy and safety of cycloferon in the combined treatment of patients with recurring anogenital herptic infection were estimated. The clinical efficacy of the combined therapy (acyclovir in a dose of 200 mg 5 times a day for 5 days + cycloferon liniment applied topically on the eruptions twice a day for 5 days) was 85% or 25% higher vs. the control.